Relationship between perception of malocclusion and the psychological impact of dental aesthetics in university students - Bellot-Arcís, Carlos (J Clin Exp Dent, 2015)
Introduction and Objectives: The objectives were to assess the relationship between perceived smile aesthetics and perceived psychological impact as measured by the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ), and their own perception of it using the Aesthetic Component of the Index of Orthodontic Treatment Need (IOTN-AC) and a Visual Analog Scale (VAS); relate the IOTN-AC and VAS to the PIDAQ; and study the predictive capacity of the scales for psychological impact. Material and Methods: A cross-sectional study was conducted in 447 college students in Spain and Portugal (average age 20.4 years, 33.1% men and 66.9% women). The online self-completed surveys used the recently-validated Spanish and Portuguese versions of the PIDAQ to assess the self–reported psychological impact of the students’ dental aesthetics and IOTN-AC and an ad hoc 100 mm VAS for their perception of their dental aesthetics. Results: PIDAQ was linearly correlated with IOTN AC and VAS. Pearson’s coefficient was 0.55 for PIDAQ and IOTN-AC (CI 95% 0.48-0.61) and -0.72 for PIDAQ and VAS (CI 95% -0.66 - -0.76). VAS and IOTN-AC were predictive variables in a linear regression model of the total PIDAQ score. The VAS diagnosed individuals whose dental aesthetics had a self-perceived psychological impact (area under the curve 0.827, CI 95% 0.787-0.868) more precisely than the IOTN-AC (area under the curve 0.742, CI 95% 0. 696-0.788). Conclusions: In adults patients, there is a significant linear relationship between perceived smile aesthetics and self-perceived psychological impact. Key words:Visual Analog Scale, Index of Orthodontic Treatment Need, malocclusion, psychological, aesthetics.